Long-term results of fallot tetralogy total correction with the use of combined pulmonary valve biological prostheses (case report) - M. F. Zinkovskyi; A. G. Goryachev; V. І. Kravchenko; S. О. Dykuha; M. Yu. Atamanyuk; О. Karimov; V. N. Hrapunov; K. B. Babadzanov (Ukrainian Journal of Cardiovascular Surgery, 2016)
Long-term survival with good clinical and hemodynamic results is shown on the example of 3 cases of Fallot tetralogy total correction with the use of personally made xenoaortic bioprostheses in the pulmonary artery position (terms of observation: 38, 37, 20 years).